2013
DOI: 10.1002/ppap.201300027
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography (TEG) Cups and Pins with Different PECVD Coatings: Effect on the Coagulation Cascade in Platelet‐poor Blood Plasma

Abstract: Thromboelastography uses cups and pins made of CyroliteW plastic to analyze the rate of fibrin clot formation in blood samples. In this study, TEG cups and pins were modified by 4 distinct coating types using plasma-enhanced chemical vapor deposition (PECVD): carboxylated, amine-rich, hydrophobic, SiO 2 , and analyzed for surface chemistry and wettability. We tested the hypothesis that the coagulation kinetics of recalcified citrated blood plasma is controlled by surface chemistry, in the absence of clot activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Caco‐2 epithelial cells were found to attach and proliferate to a similar extent on traditional cell culture plastic and PECVD‐deposited poly(2‐hydroxyethyl methacrylate) (pHEMA) films with a 1:1:1.1 ratio of carbonyl:hydroxyl:ester groups . Data in this study extend these findings to show that L‐PPE:O films with 1:1:1.9 carbonyl:hydroxyl:ester groups and 6.7% carboxylic acid support human MSC cell attachment and osteogenesis. This study also revealed that primary human MSCs colonize and commit to early osteoblast differentiation on both HMDSO surfaces (92.3° WCA) and L‐PPE:O surfaces (41.8° WCA), but after 3 weeks of osteogenic culture, end‐stage differentiation and biomineralization only takes place on L‐PPE:O surfaces, an effect enhanced by adsorption of L‐PPE:O with P15‐CSP or P15.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Caco‐2 epithelial cells were found to attach and proliferate to a similar extent on traditional cell culture plastic and PECVD‐deposited poly(2‐hydroxyethyl methacrylate) (pHEMA) films with a 1:1:1.1 ratio of carbonyl:hydroxyl:ester groups . Data in this study extend these findings to show that L‐PPE:O films with 1:1:1.9 carbonyl:hydroxyl:ester groups and 6.7% carboxylic acid support human MSC cell attachment and osteogenesis. This study also revealed that primary human MSCs colonize and commit to early osteoblast differentiation on both HMDSO surfaces (92.3° WCA) and L‐PPE:O surfaces (41.8° WCA), but after 3 weeks of osteogenic culture, end‐stage differentiation and biomineralization only takes place on L‐PPE:O surfaces, an effect enhanced by adsorption of L‐PPE:O with P15‐CSP or P15.…”
Section: Discussionsupporting
confidence: 66%
“…Hydrophobic thin films with a poorly wettable surface were generated by plasma‐polymerized hexamethyldisiloxane (HMDSO) . In previous studies, L‐PPE:O but not HMDSO surfaces were shown to reproducibly initiate contact activation of the blood coagulation enzyme cascade; these data serve as proof‐of‐concept that L‐PPE:O thin films present anionic surfaces that can form bioactive complexes with proteins such as FXII. Thus, we analyzed the effect of P15‐CSP, P15, CSP coatings on surfaces with distinct wettability, including highly anionic (L‐PPE:O), anionic (TC‐treated), and hydrophobic (HMDSO).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Chief among these is the need for contact containment and manipulation of the blood sample. Blood contact with container walls has a strong effect on initiation of the coagulation cascade, even in the presence of calcium chloride (CaCl 2 ), resulting in sensitivity of coagulation tests to the types of material and surface treatment used for the containment cup . These effects also lead to widely variable clot rigidity and variations in the quality of clot adhesion to the cup walls .…”
Section: Introductionmentioning
confidence: 99%